[Supplemental material] Experimental, DFT study, and in silico molecular docking investigations of dichlorodiphenyltrichloroethane against human estrogen receptor alpha - Ntui, Tabe Ntui; Osabor, Vincent Ndem; Neji, Peter Amba; Akpe, Michael Akomaye; Agwupuye, John Akwagiobe; Adalikwu, Stephen Adie; Gber, Terkumbur Emmanuel; Andrew, Bitrus Hyelavalada; Ugbaja, Uduak (Eclética Química, 2022)
Advanced computational tools allowed to study a pure commercial sample of dichlorodiphenyltrichloroethane (DDT) prepared in liquid phase in KBr pellets and characterized using FT-IR and GC-MS followed by the application of DDT for molecular docking against human estrogen receptor alpha. The compound was modelled using GaussView software. Using Veda 04 program, the theoretical vibrational energy distributions and experimental vibrational frequencies were compared. Interestingly, C1 and C2 possess the highest atomic charge density distribution (ACDD) of -0.284e and -0.283e while C21 and C11 have lowest ACDD of -0.064e and -0.063e in a relative manner, since the deactivating power of chlorine atoms decreases charge densities of the bonded carbon. The highest intramolecular interacting perturbation energy is 1121.92 kJ mol–1 occurs between π*C19–C21 donor orbital and π*C14–C16 acceptor orbital while the least intramolecular interaction occurs in the lone pair of LPC26 and the sigma nonbonding (𝜎C1–Cl24) NBO orbitals with E(2) of 32.21 kJ mol–1. Steric interaction was the only interaction found within the complex after the docking.